1998
DOI: 10.1080/741941599
|View full text |Cite
|
Sign up to set email alerts
|

The Spacing Effect Depends on an Encoding Deficit, Retrieval, and Time in Working Memory: Evidence

Abstract: The spacing effect in list learning occurs because identical massed items suffer encoding deficits and because spaced items benefit from retrieval and increased time in working memory. Requiring the retrieval of identical items produced a spacing effect for recall and recognition, both for intentional and incidental learning. Not requiring retrieval produced spacing only for intentional learning because intentional learning encourages retrieval. Once-presented words provided baselines for these effects. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…In the laboratory studies, this issue was not ignored; changes in the environment, the internal state of the subject, and the context of the surrounding material were all considered in theories of how the repetition and spacing of individual presentations affected later episodic memory for the occurrence of an item (e.g., Braun & Rubin, 1998; Glenberg, 1979; Watkins & Kerkar, 1985). Within the autobiographical memory literature, Barsalou (1988) provided another approach to examining repeated events by extending the concept of basic levels in knowledge (Rosch, Mervis, Gray, Johnson, & Boyesbraem, 1976) to events.…”
Section: The Construction Of a Single Instance From Knowledge And Repmentioning
confidence: 99%
“…In the laboratory studies, this issue was not ignored; changes in the environment, the internal state of the subject, and the context of the surrounding material were all considered in theories of how the repetition and spacing of individual presentations affected later episodic memory for the occurrence of an item (e.g., Braun & Rubin, 1998; Glenberg, 1979; Watkins & Kerkar, 1985). Within the autobiographical memory literature, Barsalou (1988) provided another approach to examining repeated events by extending the concept of basic levels in knowledge (Rosch, Mervis, Gray, Johnson, & Boyesbraem, 1976) to events.…”
Section: The Construction Of a Single Instance From Knowledge And Repmentioning
confidence: 99%
“…Considerable evidence shows that repeated study improves memory (e.g., Braun & Rubin, 1998;Crowder, 1976;Greene, 1989). Classic work by Rundus ( 1971 ) has further shown that repetition of words promotes more rehearsals of those words, and increased rehearsals are associated with better organization of the words.…”
Section: The Importance Of Study and Retrieval Repetitions In Shapingmentioning
confidence: 99%
“…It is well-established in educational fields that concentrated instruction that takes place in a short period of time may have little effect on long-term retention (e.g., Bellezza & Young, 1989;Braun & Rubin, 1998;Challis, 1993). Students who 'cram' might do well on an exam that takes place shortly after the cramming session, but retain little of the information over long periods of time (Santrock & Halonen, 2002).…”
Section: Did He Have His Clothes On? What Is His Name?)mentioning
confidence: 99%